Akumulasi Logam Berat dan Efeknya Terhadap Morfologi Tulang Sirip Keras Ikan Sembilang (Plotosus canius Web & Bia) di Muara Sungai Kahayan dan Katingan, Kalimantan Tengah - Edison Harteman (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2012)
The study was conducted in the estuarine Kahayan and Katingan, Central Kalimantan. This study aim was to evaluate the content, distribution and effects of Pb, Hg and Cd on bone tissue and Catfish hard fins morphology. Study of content, the distribution of accumulated Pb, Hg and Cd conducted to provide information to the public about the characteristics of Catfish containing Pb, Hg and Cd. Results showed that Catfish hard fins bone containing Pb > Hg > Cd. Distribution of accumulated Pb, Hg and Cd in hard fins bone tissue tend to occur in clusters than random. Accumulation of Pb in hard fins bone tissue associated with Hg and Cd. Association of Pb, Hg and Cd in hard fins bone tissue occur clustered in a location over the role in inducing hard fins bone abnormal morphology. Effects of Pb, Hg and Cd accumulation in Catfish hard fins bone tissue cause its twisted irregular, partial bone hard fin thick and thin, hollow, appearing bumps, and abnormal bone jagged, brittle and easily broken. Abnormal growth of hard fins bone tissue, as found in normal bone hard fins.